Widening the scope of mental health with a ‘youth centred’ approach: a qualitative study involving health care professionals in Sweden’s youth clinics - Isabel Goicolea; Linda Richter Sundberg; Maria Wiklund; Anne Gotfredsen; Monica Christianson (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The aim of this study was to explore how health care providers at youth clinics (YCs) in Sweden engage with, focus on, and navigate across the mental health youth space, while upholding the core bedrock principle of “youth-centeredness”. Methods Qualitative interviews were conducted with 21 health care professionals working in three YCs located in three different regions of Sweden. Data were analysed using reflexive thematic analysis informed by the work of Braun and Clarke. Results The three themes were: 1) “youth mission—at the core of the YCs” work and challenged by a stronger involvement in mental ill health’; 2) “YCs” unique and complementary role in the youth mental health system: a holistic perspective, team work, and a focus on normalization’, and 3) “Caught between a rock and a hard place: to treat at a care level that is not optimal for the young users” needs or to refer within an unreliable system’. Conclusion This study reflects the individuality and key features of YCs, their widening roles within the mental health sphere, and the challenges faced in maintaining and expanding the characteristic “youth-centred” approach while expanding their work with mental health.